2001
DOI: 10.1263/jbb.92.360
|View full text |Cite
|
Sign up to set email alerts
|

Kojic Acid Production in an Airlift Bioreactor Using Partially Hydrolyzed Raw Corn Starch.

Abstract: In a culture of Aspergillus oryzae MK-107-39 in a 3-l airlift bioreactor, kojic acid was not produced when glucose/wheat germ medium (GM1) was used. However, when a jar fermentor was used, the kojic acid yield was high. A suitable medium for culture in an airlift bioreactor consisting of partially hydrolyzed corn starch and a small amount of corn steep liquor (CSL) (SM1) was selected. In the cultivation in the airlift bioreactor using SM1, nearly 40 g/l of kojic acid was produced, which was the same as the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…They attribute this reduction to degradation of kojic acid to oxalic and acetic acid by the mycelium under glucose depleted conditions [23, 31, 54, 55]. Futamura et al [56] produced kojic acid by A. oryzae MK-107-39 in a jar fermentor and recorded that level of kojic acid reached up to 40 g/L. On the other hand, Wakisaka et al [42] produced kojic acid by A. oryzae NRRL 484 using continuous membrane surface liquid culture technique and recorded that kojic acid concentration reached 45 mg/mL medium and nearly constant after 15 days of cultivation for over 70 days.…”
Section: Resultsmentioning
confidence: 99%
“…They attribute this reduction to degradation of kojic acid to oxalic and acetic acid by the mycelium under glucose depleted conditions [23, 31, 54, 55]. Futamura et al [56] produced kojic acid by A. oryzae MK-107-39 in a jar fermentor and recorded that level of kojic acid reached up to 40 g/L. On the other hand, Wakisaka et al [42] produced kojic acid by A. oryzae NRRL 484 using continuous membrane surface liquid culture technique and recorded that kojic acid concentration reached 45 mg/mL medium and nearly constant after 15 days of cultivation for over 70 days.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the transcription level of the enzyme and the transporter were enhanced by an over-expression of the transcription factor, which correlates well with that report. Although there are reports of improved kojic acid productivity through fermentation engineering strategies [1,5,23], to our knowledge, this study is the first to report an improvement in kojic acid productivity via genetic engineering. Kojic acid productivity could be improved even more by combining fermentation engineering and genetic engineering in future work.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, it has some unique properties. Futamura et al [5] reported that the production cost of kojic acid is about $10/kg. It must be decreased to less than $2/kg before it could be used in many applications.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the three genes encode an oxidoreductase, a Zn(II) 2 -Cys 6 (C6)-type transcription factor, and a major facilitator superfamily transporter [10], [11]. KA production is typically observed after 3 to 4 days of inoculation of A. oryzae in liquid growth media, and can be stopped by adding a small amount of sodium nitrate to the medium [21], [22].…”
Section: Resultsmentioning
confidence: 99%